2010
DOI: 10.1002/cmmi.402
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhancement by differently sized paramagnetic MRI contrast agents in mice with two phenotypes of atherosclerotic plaque

Abstract: Interest in the use of contrast-enhanced MRI to enable in vivo specific characterization of atherosclerotic plaques is increasing. In this study the intrinsic ability of three differently sized gadolinium-based contrast agents to permeate different mouse plaque phenotypes was evaluated with MRI. A tapered cast was implanted around the right carotid artery of apoE(-/-) mice to induce two different plaque phenotypes: a thin cap fibroatheroma (TCFA) and a non-TCFA lesion. Both plaques were allowed to develop over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
(44 reference statements)
2
27
0
Order By: Relevance
“…Previous studies have demonstrated that targeted iron-oxide-based MR-contrast agents are able to create hypo-intense signals on T 2 * -weighted images in regions of VCAM-1 or P-selectin expression in mouse models of atherosclerosis and brain inflammation [17-19]. Alternatively, the use of targeted Gd-based probes, which create signal hyperenhancement on T 1 -weighted images, has been explored as well [20-22]. Choi et al used anti-ICAM-1 antibodies decorated with Gd-DTPA moieties to highlight muscular inflammation on in vivo MRI, whereas Sipkins et al performed ex vivo MRI to visualize brain inflammation using paramagnetic liposomes [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that targeted iron-oxide-based MR-contrast agents are able to create hypo-intense signals on T 2 * -weighted images in regions of VCAM-1 or P-selectin expression in mouse models of atherosclerosis and brain inflammation [17-19]. Alternatively, the use of targeted Gd-based probes, which create signal hyperenhancement on T 1 -weighted images, has been explored as well [20-22]. Choi et al used anti-ICAM-1 antibodies decorated with Gd-DTPA moieties to highlight muscular inflammation on in vivo MRI, whereas Sipkins et al performed ex vivo MRI to visualize brain inflammation using paramagnetic liposomes [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we introduce a novel liposomal contrast agent functionalized with anti-ICAM-1 (aICAM-1) antibodies for sensitive multimodal magnetic resonance imaging (MRI) and fluorescence imaging of endothelial ICAM-1 expression. MRI enables in vivo high-resolution imaging of ICAM-1 expression in an anatomical context, whereas ex vivo fluorescence microscopy can be used to study the spatial distribution of the liposomes at the tissue and cellular level [9]. Because of the relatively large diameter of the liposomes (100–150 nm), passive extravasation from the blood is expected to be minimal and liposomes will be largely confined to the blood pool, which facilitates the detection of intravascular targets such as ICAM-1.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the larger size of nanocarriers promotes a higher level of uptake in diseased tissues by the enhanced permeability and retention (EPR) effect [6,7]. Importantly, to address the inflammatory response in cardiovascular disease, the drug-containing nanocarriers should be delivered with high specificity to inflammatory cells in the diseased tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Size-dependent contrast uptake by plaque-associated macrophages remains a contentious topic. A comprehensive study evaluated three forms of gadolinium: unencapsulated form (Gd-HP-DO3A), in association with micelles (~15 nm) and encapsulated in liposomes (~125 nm) in atherosclerotic mice [17]. The unencapsulated form rapidly entered the aortic wall but washed out within an hour and the micelles were retained within the aortic wall for up to 24 hours.…”
Section: Discussionmentioning
confidence: 99%